The impact of nutritional status on the outcomes of cancer patients such as mortality, survey and length of hospitalization in palliative care - Avcı, Deniz; Çetinkaya, Ali (The European Research Journal, 2019)
Objectives: The aim of this study was to determine the effects of nutritional status of the cancer patients in the palliative unit on some important outcomes such as mortality, hospitalization periods and survey.Methods: The study was carried out through a retrospective review of 65 cancer patients who were treated at the palliative care center. The age and gender of the patients, the type of cancer, the place where they are referred to the palliative unit (from home or from the hospital), from which unit they came from (oncology, intensive care unit, other services), the length of stay, how long they lived after discharge, how long each patient lived after the palliative unit hospitalization day and the NRS-2002 scores were recorded.Results: There was a statistically significant difference between the median hospital duration of the home-based patients and the median duration of hospital-based patients (11 [2-42] days versus 22 [2-180] days) (p = 0.001). The mean survival time of the home-based patients was median 87.5 (2-323) days, while this was 9 (2-104) days in hospital-based patients (p = 0.017). While 29.5% (n = 13/27) of the patients coming from the house died in the palliative care center, it was 70.5% in the patients taken from the hospital (p = 0.002). The NRS-2002 scores of the cancer patients who were followed up at the palliative unit were correlated with the age of the patients (r = 0.365, p = 0.003). Conclusions: We concluded that the patients who came to palliative care from home have better surveys than the ones came from the hospital.